Effects of Slip, Brownian Motion and Thermophoresis on Peristaltic Pumping of Nano Fluid in an Asymmetric Channel with Porous Medium - Sreenadh, S.; Yasodhara, G.; Sumalatha, B.; N.S.Srinivas, A. (International Journal of Engineering and Technology, 2018)
This paper deals with peristaltic motion of electrically conducting nanofluid in a tapered asymmetric channel through a porous medium in presence of heat and mass transfer under the effect of slip conditions. The problem is reduced mathematically by a set of nonlinear partial differential equations which describe the conservation of mass, momentum, energy and concentration of nanoparticles. The non-dimensional form of these equations is simplified under the assumption of long wavelength and low Reynolds number. The coupled governing equations are solved analytically. The expressions for velocity, stream function, temperature and concentration are derived. The results have been presented graphically for the various interested emerging parameters and the obtained results are discussed in detail. It is observed that the magnitude of the velocity decreases in the middle of the channel while it increases near the channel walls with an increase in the non-uniform parameter Â It is also noticed that the nanoparticle temperature increases with increasing thermal slip parameter . The present result coincides with the findings of Kothandapani and Prakash [19].Â Â